Risk levels for suffering a traffic injury in primary health care. The LESIONAT* project - Bel Jordi; Marques Fernando; Garcia-Ortiz Luis; Perez Katherine; Valiente Susana; Roig Lydia; Prieto-Alhambra Daniel; Martín-Cantera Carlos; Mundet Xavier; Bonafont Xavier; Birules Marti; Soldevila Núria; et al. (BMC, 2010)
Abstract Background Literature shows that not only are traffic injuries due to accidents, but that there is also a correlation between different chronic conditions, the consumption of certain types of drugs, the intake of psychoactive substances and the self perception of risk (Health Belief Model) and the impact/incidence of traffic accidents. There are few studies on these aspects in primary health care. The objectives of our study are: Main aim: To outline the distribution of risk factors associated with Road Traffic Injuries (RTI) in a driving population assigned to a group of primary health care centres in Barcelona province. Secondly, we aim to study the distribution of diverse risk factors related to the possibility of suffering an RTI according to age, sex and population groups, to assess the relationship between these same risk factors and self risk perception for suffering an RTI, and to outline the association between the number of risk factors and the history of reported collisions. Methods/Design Design: Cross-sectional, multicentre study. Setting: 25 urban health care centres. Study population: Randomly selected sample of Spanish/Catalan speakers age 16 or above with a medical register in any of the 25 participating primary health care centres. N = 1540. Unit of study: Basic unit of care, consisting of a general practitioner and a nurse, both of whom caring for the same population (1,500 to 2,000 people per unit). Instruments of measurement: Data collection will be performed using a survey carried out by health professionals, who will use the clinical registers and the information reported by the patient during the visit to collect the baseline data: illnesses, medication intake, alcohol and psychoactive consumption, and self perception of risk. Discussion We expect to obtain a risk profile of the subjects in relation to RTI in the primary health care field, and to create a group for a prospective follow-up. Trial Registration Clinical Trials.gov Identifier: NCT00778440.